A readequação do descarte das matérias-primas utilizadas na fabricação de estofados e de artigos para decoração em roupas de festas - Alexandrino, Carolina Anastacio (2013)
This project is meant to develop a collection of clothes for parties of proposed development. To do so, based on the idea of working with leather retrace discarded by the industrial and automotive and furniture industry with leftover materials used in the manufacture of articles for decoration. The context of innovation is inserted in the clothing parties the use of unconventional materials for the manufacture of the product life cycle and propose to the higher parts, with the introduction of a multi-use concept models.